Team topologies organizing business and technology teams for fast flow - Skelton, Matthew; Pais, Manuel (IT Revolution, 2019)
"In Team Topologies, DevOps consultants Matthew Skelton and Manuel Pais share secrets of successful team patterns and interactions to help IT organizations choose and evolve the right team patterns to ensure success, making sure to keep the software healthy and to optimize for value streams. Team Topologies will help readers discover: - Team patterns used by successful organizations. - Common team patterns to avoid with modern software systems. - When and why to use different team patterns - How to evolve teams effectively. - How to split software and align to teams"--
Includes bibliographical references and index. - Online resource; title from digital title page (viewed on October 22, 2019)
Keywords: Information technology -- Management; Teams in the workplace -- Management; Computer software -- Development -- Management; Technologie de l'information; Gestion; Équipes de travail; Gestion; Teams in the workplace; Management; Information technology; Management; Computer software; Development; Management; Organizational change; Software engineering; Management; Teams in the workplace